Doctor Strange. 2 - Waid, Mark, 1962-; Howard, Tini; Pichetshote, Pornsak; Lee, Stan, 1922-2018; Ditko, Steve (Marvel Worldwide, Inc., 2024)
When an alien sorcerer demands Stephen's help saving his far-off planet from the World-Eater, Galactus ends up banished to the darkest depths of the mystic realms! Now, with his powers depleted, Strange must undertake a rescue mission like never before! Then, a truly terrifying villain works their way into the Marvel Universe via a small house in Kansas, and their impact will be huge! And with his hands healed after so many years of pain, Stephen can return to his old life as a Surgeon Supreme! But torn between his obligations, which solemn oath will he choose to uphold? Join Stephen Strange, M.D., for a new era of modern medicine, mystic arts...and horror!